2019
DOI: 10.1016/j.bbr.2018.12.052
|View full text |Cite
|
Sign up to set email alerts
|

Adeno-associated viral overexpression of neuroligin 2 in the mouse hippocampus enhances GABAergic synapses and impairs hippocampal-dependent behaviors

Abstract: The cell adhesion molecule neuroligin2 (NLGN2) regulates GABAergic synapse development, but its role in neural circuit function in the adult hippocampus is unclear. We investigated GABAergic synapses and hippocampus-dependent behaviors following viral-vector-mediated overexpression of NLGN2. Transducing hippocampal neurons with AAV-NLGN2 increased neuronal expression of NLGN2 and membrane localization of GABAergic postsynaptic proteins gephyrin and GABA A Rγ2, and presynaptic vesicular GABA transporter protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 113 publications
2
5
0
Order By: Relevance
“…The present study confirmed that exogenous NL2 was expressed on neurons and colocalized with gephyrin, a GABAergic postsynaptic protein. This finding is consistent with a previous study reporting that AAV vector‐mediated local gene delivery of NL2 into hippocampal neurons increased the neuronal expression of NL2, gephyrin and GABAARγ2, suggesting trans‐synaptic enhancement of GABAergic synapses 47 …”
Section: Discussionsupporting
confidence: 93%
“…The present study confirmed that exogenous NL2 was expressed on neurons and colocalized with gephyrin, a GABAergic postsynaptic protein. This finding is consistent with a previous study reporting that AAV vector‐mediated local gene delivery of NL2 into hippocampal neurons increased the neuronal expression of NL2, gephyrin and GABAARγ2, suggesting trans‐synaptic enhancement of GABAergic synapses 47 …”
Section: Discussionsupporting
confidence: 93%
“…Reduced NLGN2 expression in the prefrontal cortex (PFC) is involved in attention deficits induced by peripubertal stress which can be reversed by virus-mediated NLGN2 rescue (Tzanoulinou et al, 2016). Animal models using the genetic engineering method showed that Nlgn 2 R215H knock-in (KI) mouse exhibited schizophrenia-like behaviors and higher anxiety behaviors with significant reduction of mIPSCs in the dentate gyrus (DG), reduced subunit GABA-A γ2 expression levels, and reduced presynaptic PV and VGAT levels, while there were no changes of miniature excitatory postsynaptic currents (mEPSCs), vesicular glutamate transporter (VGLUT), and postsynaptic density protein 95 (PSD95) expression levels (Jiang et al, 2018;Van Zandt et al, 2019). NLGN2 of ACC is involved in KCC2-mediated abnormal GABAergic transmission induced aggressive behaviors (Jager et al, 2020).…”
Section: Nlgn2 3 Andmentioning
confidence: 99%
“…Two studies have investigated AAV-mediated overexpression of NL2 in the hippocampus. In one study, overexpression of NL2 results in increased gephyrin clusters and VGAT+ puncta by confocal microscopy immunofluorescence and an increase in the gephyrin, VGAT and GABA A R-γ2 subunit protein expression by western blot, suggesting a strengthening inhibitory synapses in the transduced neurons (Van Zandt et al, 2019). In the other study, increased NL2 expression leads to increased mRNA levels for GAD65, but no increase in neurexin-1, gephyrin, or GAD67 mRNAs (Kohl et al, 2013).…”
Section: Discussionmentioning
confidence: 96%